1998
DOI: 10.1021/jf970364j
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Capillary GC−GC for the Analysis of Real Complex Samples. 3. Enantiomeric Distribution of Monoterpene Hydrocarbons and Monoterpene Alcohols of Mandarin Oils

Abstract: The enantiomeric distribution of beta-pinene, sabinene, limonene, linalool, terpinen-4-ol, and alpha-terpineol in mandarin oils has been determined using a fully-automated, multidimensional, double-oven GC-GC system. This system allows fractions to be multitransferred during the same GC analysis and the use of the two GCs independently when the multitransfer option is not used. The results obtained allowed the characterization of mandarin essential oil and the determination of extraneous oils added to or conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 19 publications
5
19
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10] Some relatively recent papers have reported the on-line HPLC preseparation/concentration and HRGC analysis of various volatile fractions in a fully automated mode. [3][4][5][6] These effective separations have concerned monoterpene and sesquiterpene hydrocarbons and their oxygenated derivatives, as well as aliphatic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] Some relatively recent papers have reported the on-line HPLC preseparation/concentration and HRGC analysis of various volatile fractions in a fully automated mode. [3][4][5][6] These effective separations have concerned monoterpene and sesquiterpene hydrocarbons and their oxygenated derivatives, as well as aliphatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Several successful applications, especially chiral ones, have been reported in literature. [8][9][10] Although MDGC is a valuable analytical tool, it is also characterized by a few drawbacks, such as high time costs, complex instrumentation and the fact that the 2-D advantage cannot be exploited by all 1-D peaks.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chanegriha et al separated successfully a synthetic mixture of 19 constituents found in essential oils using the coupled columns in series, 13 of which were not separated on a single column [4]. Multi-dimensional gas chromatography (MDGC) has also been used in the analysis of essential oils [5][6][7]. These methods extend the separation power of capillary GC and clearly resolve the selected constituents in a GC chromatogram, but as Giddings stated, twodimensional continuous (and coupled column) separation had not been developed to reach its potential in chromatography [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when the system was not used in the multidimensional configuration, the two gas chromatographs could be used at the same time independently without any change in the hardware. This system has been used for the determination of the enantiomeric distribution of monoterpene hydrocarbons and monoterpene alcohols in lime [2] and mandarin [3] essential oils. In this paper some changes made in the pneumatic and electronic circuits to simplify the use of the instrumentation and improve his reliability are described.…”
Section: Introductionmentioning
confidence: 99%